2019
DOI: 10.1007/s12015-019-09926-y
|View full text |Cite|
|
Sign up to set email alerts
|

The Intrapericardial Delivery of Extracellular Vesicles from Cardiosphere-Derived Cells Stimulates M2 Polarization during the Acute Phase of Porcine Myocardial Infarction

Abstract: Acute myocardial infarction triggers a strong inflammatory response in the affected cardiac tissue. New therapeutic tools based on stem cell therapy may modulate the unbalanced inflammation in the damaged cardiac tissue, contributing to the resolution of this pathological condition. The main goal of this study was to analyze the immunomodulatory effects of cardiosphere-derived cells (CDCs) and their extracellular vesicles (EV-CDCs), delivered by intrapericardial administration in a clinically relevant animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 44 publications
(61 reference statements)
1
31
0
Order By: Relevance
“…Recently, Lopez et al [ 36 ] investigated the effects of an intrapericardial injection of CDCexo 72 h after AMI ( n = 18) [ 37 ]. Blood sampling 24 h after treatment revealed an increase in circulating anti-inflammatory CD14+ CD163+ M2 macrophages in the treatment group, as well as an upregulation of arginase-1, which is considered an M2-differentiation marker, in the pericardial fluid.…”
Section: Cell-free Cardiac Regeneration Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Lopez et al [ 36 ] investigated the effects of an intrapericardial injection of CDCexo 72 h after AMI ( n = 18) [ 37 ]. Blood sampling 24 h after treatment revealed an increase in circulating anti-inflammatory CD14+ CD163+ M2 macrophages in the treatment group, as well as an upregulation of arginase-1, which is considered an M2-differentiation marker, in the pericardial fluid.…”
Section: Cell-free Cardiac Regeneration Therapiesmentioning
confidence: 99%
“…Blood sampling 24 h after treatment revealed an increase in circulating anti-inflammatory CD14+ CD163+ M2 macrophages in the treatment group, as well as an upregulation of arginase-1, which is considered an M2-differentiation marker, in the pericardial fluid. While they successfully demonstrated that a minimally invasive intrapericardial adminstration of CDCexo was safe and had a local and systemic effect on inflammatory cells, they did not find any significant differences in LVEF or infarct size 10 weeks after treatment [ 37 ].…”
Section: Cell-free Cardiac Regeneration Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Observed variations documented by the findings of various completed and ongoing clinical trials 1 3 , 12 that have been/are focusing on mesenchymal SCs, cardiac progenitor cells (CPCs), embryonic stem cells (ESCs), and inducible pluripotent SCs (iPSCs) ( Table 1 ) may be attributed to (among others) the differences in the design and cell preparation parameters, suitable cell type(s), administration route(s), delivery time 13 , and end points 12 . The existing hypotheses for documented SC effects include (a) direct (cardiomyogenesis and vasculogenesis) and (b) indirect (attenuation of inflammatory responses and fibrosis, promotion of angiogenesis, and enhancement of cellular viability via paracrine/other signaling/post-translational modification mechanisms) mechanisms 12 , 14 , 15 . Despite the ambivalent clinical outcomes, preclinical successes have been documented in rodents and mammals, as manifested by feasible and safe SC administration, the capacity to change the course of the MI, and improved remodeling and cardiac functional indices (e.g., ejection fraction, ventricular volumes, etc.)…”
Section: Cardiac Stem Cell Therapymentioning
confidence: 99%
“…Overall, iPSCs 13 , 14 are more advantageous but still face critical challenges 21 that can be potentially addressed with next generation therapies, including polymeric biodegradable scaffolds and three-dimensional constructs. These constitute optimal test beds that can be used to mediate the proinflammatory/fibrotic/apoptotic responses, in combination with the use of cytokines, microribonucleic acid (miRNA), growth factors, noncoding RNA constructs, and extracellular vesicles, to achieve improved engraftment 1 , 22 and viability under hypoxic states, immunogenicity, electrical topology 23 , cellular differentiation 24 , and the elimination of arrythmogenic events 19 .…”
Section: Cardiac Stem Cell Therapymentioning
confidence: 99%